Removal of Heavy Metals by Bacteria in Bio-Ceramsite and their Toxicity to Bacteria - Shi, Yan; Qi, Xuebin; Gao, Qing (Asian Journal of Chemistry, 2015)
Heavy metal pollution has become one of the global environmental pollution problems of concern. Bio-ceramsite technology is one of the most effective technologies in pretreatment of drinking water. This technology can be employed to remove heavy metals and organic pollutants from water. In this paper, Pb(II) and Cd(II) adsorption by the bio-ceramsite with Citrobacter freundii (C. freundii) immobilization was studied. The findings of the current study suggest that the bio-ceramites showed biosorption abilities for Cd(II) and Pb(II) and the removal efficiency for Pb(II) is lower than Cd(II). The adsorption mechanism can be attributed to electrostatic attraction and covalent bond. The morphology of the cells changed after the adsorption of Cd(II) and Pb(II) due to the dissociation of the assembly of peptidoglycan and lipopolysaccharide. The fluorescence polarization has shown a significant decrease in membrane fluidity and the increase of permeability of cell membrane. The spectral profile of C. freundii suggests the alteration of carbonyl, amide and phosphonic group on the cell membrane.